PENGARUH PEMBERIAN PUPUK ORGANIK CAIR MEREK NASA TERHADAP PERTUMBUHAN BIBIT TREMBESI (Samanea saman) di SHADEHOUSE FAKULTAS KEHUTANAN UNIVERSITAS LAMBUNG MANGKURAT - Awaliah Awaliah; Damaris Payung; Adistina Fitriani (Universitas Lambung Mangkurat, 2020)
The purpose of this research is to know the effect of liquid compost fertilizer on growth of Samanea saman seedlings, some parameters of growth such as life percentage, height, number of leaves are measured and diameter increament. Is used in the research Completely Randomized Design (CRD) with 4 treatments and 10 replications. The reseach results showed that the height, number of leaves and diameter have a significant difference among the four parameters of growth.Keywords: Influence; liquid fertilizer; NASA; trembesi